Unveiling the chemical kinetics of aminomethanol (NH2CH2OH): insights into O.H and O2 photo-oxidation reactions and formamide dominance - Nulakani, Naga Venkateswara Rao; Ali, Mohamad Akbar (Frontiers in Chemistry, 2024)
In this study, we have expounded the chemical kinetics of aminomethanol in the reaction pathways initiated by the hydroxyl radical (O ̇H) with the aid of ab initio//density functional theory (DFT) i.e., coupled-cluster theory: (CCSD(T))//hybrid-DFT:(M06-2X/6-311++G(3df,3pd). We have explored various possible directions of the O ̇H radical on aminomethanol, as well as the formation of distinct pre-reactive complexes. Our computational findings reveal that the H transfer necessitates activation energies ranging from 4.1–6.5 kcal/mol from the –CH2 group, 3.5–6.5 kcal/mol from the –NH2 group and 7–9.3 kcal/mol from the –OH group of three rotational conformers. The H transfer from –CH2, –NH2 and –OH exhibits an estimated total rate constant (kOH) of approximately 1.97 × 10-11 cm3 molecule−1 s−1 at 300 K. The branching fraction analysis indicates a pronounced dominance of C-centered NH2C ̇HOH radicals with a favorability of 77%, surpassing the N-centered N ̇HCH2OH (20%) and O-centered NH2CH2O ̇ (3%) radicals. Moreover, our investigation delves into the oxidation of the prominently favored carbon-centered NH2C ̇HOH radical through its interaction with atmospheric oxygen molecules. Intriguingly, our findings reveal that formamide (NH2CHO) emerges as the predominant product in the NH2C ̇HOH + 3O2 reaction, eclipsing alternative outcomes such as amino formic acid (NH2COOH) and formimidic acid (HN=C(H)-OH). At atmospheric conditions pertinent to the troposphere, the branching fraction value for the formation of formamide is about 99%, coupled with a rate constant of 5.5  10-12 cm3 molecule−1 s−1. Finally, we have scrutinized the detrimental impact of formamide on the atmosphere. Interaction of formamide with atmospheric hydroxyl radicals could give rise to the production of potentially perilous compounds such as HNCO. Further, unreacted N ̇HCH2OH radicals may initiate the formation of carcinogenic nitrosamines when reacting with trace N-oxides (namely, NO and NO2). This, in turn, escalates the environmental risk factors.